Present-day crustal movement of the Chinese mainland based on Global Navigation Satellite System data from 1998 to 2018. Issue 2 (15th January 2019) - Yu, Jiansheng; Tan, Kai; Zhang, Caihong; Zhao, Bin; Wang, Dongzhen; Li, Qi
Abstract: A total of more than 260 continuous stations and 2000 campaign stations from the Crustal Movement Observation Network of China (CMONOC) project, covering the Chinese mainland and its surrounding areas during the period of 1998–2018, are processed using the Bernese Global Navigation Satellite System (GNSS) software via a state-of-the-art method. We obtain the coordinate time series of all the stations given in the reference frame ITRF2014, estimate the coseismic deformation, and remove outliers. Lastly, we present the latest, most complete, and most accurate contemporary horizontal velocity field with respect to the stable Eurasian plate, irrespective of the postseismic deformations. This study shows that the signal of tectonic movement in Western China is stronger than that in Eastern China particularly in the Tibetan Plateau, with a rate of 18–32 mm/a. Moreover, the signal decays sharply from south to north. However, North China and South China move coherently to the ESE direction mostly at a rate of 4–10 mm/a and have not experienced any abrupt velocity gradients in their interiors. Meanwhile, Northeast China has the lowest velocity of only 2–4 mm/a in addition to the coastal areas that have slightly larger velocities. The densified and continuous observation of GNSS stations are of great significance to the study of the present-day crustal movement and tectonic deformation characteristics of the Chinese mainland. This would help to provide better constraints on the kinematics and dynamics of the region.